2011
DOI: 10.1177/0333102411409074
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular sensitivity in vestibular migraine: VEMPs and motion sickness susceptibility

Abstract: The results indicate more pathology in the VEMP circuitry in migraineurs than in healthy controls. We did not find support for peripheral vestibular hypersensitivity in terms of lower VEMP threshold among VM patients, but they are more sensitive for motion triggers than other migraineurs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
46
2
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(55 citation statements)
references
References 40 publications
4
46
2
3
Order By: Relevance
“…Their findings may be due to shared pathophysiology. Additionally, 36% of patients with migraine-associated vertigo had prolonged p13 latencies; these patients may have brainstem lesions, showing differences in the etiology of VM [21] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Their findings may be due to shared pathophysiology. Additionally, 36% of patients with migraine-associated vertigo had prolonged p13 latencies; these patients may have brainstem lesions, showing differences in the etiology of VM [21] .…”
Section: Discussionmentioning
confidence: 99%
“…Boldingh et al [21] applied acoustic stimuli tone bursts to patients with migraine-associated vertigo and Meniere's disease; they calculated a decreased slope of 500-1000 Hz in the cVEMP responses of these patients. Their findings may be due to shared pathophysiology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Migraine patients with vertigo have been reported to have a 20%-25% prevalence of caloric hypofunction, indicating involvement of the horizontal semicircular canals [5,7,15] . cVEMP abnormalities, including absent or delayed cVEMPs [16,17] or cVEMPs of normal latency but reduced amplitude, have been reported in different studies [18] , which were proposed to indicate lesions of the sacculocollic pathways in the brainstem or saccular damage. On the other hand, in the two latest studies, cVEMPs of normal latency and amplitude have been reported in patients with VM [19,20] .…”
Section: Discussionmentioning
confidence: 98%
“…The pathogenesis is uncertain, but migraine mechanisms may interfere with the vestibular system at the labyrinth, brainstem, and cerebral cortex [7,8] . Inevitably, several studies have been performed to assess vestibulo-ocular, vestibulo-collic, and vestibulospinal functions in patients with migraine by using caloric tests, cervical vestibular evoked myogenic potentials (cVEMPs), and posturography, with results indicating peripheral, central, or combined vestibular deficits [5,7,[12][13][14][15][16][17][18][19][20] . Motion detection thresholds have also been studied [21] .…”
Section: Introductionmentioning
confidence: 99%